GAMBARAN EPIDEMIOLOGI KEJADIAN DEMAM BERDARAH DENGUE: KARAKTERISTIK PENDERITA, WAKTU DAN FAKTOR LINGKUNGAN DI KECAMATAN TEMBALANG TAHUN 2019 - Ikhwa Atika Sury; Martini Martini; Sri Yuliawati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Dengue Hemorrhagic Fever (DHF) is an endemic infectious disease in Tembalang District, Semarang. DHF is caused by dengue virus and transmitted by Aedes sp. mosquitoes especially Aedes aegypti. Patient characteristics, season, physical environmental factors and populations density is one of the risk factors for DHF transmission. This study aims to describe epidemiology of patient characteristics, time, physical environmental factors and population density on DHF incidence and analyze the correlation of factors and DHF incidence in Tembalang District. The type of this research is observasional descriptive with cross sectional study design. Samples of this research is 122 verified cases by Health Office Semarang City and they who live on Tembalang District. The epidemiological analysis obtained that the highest percentage of DHF patient is 61,5% in the male gender, 59% at the age of 4-12 years old and 63,1% during the rainy season. The result of statistical analysis show that there is no correlation between area height (p = 0,084), temperature (p = 0,823), rainfall (p = 0,692), land use (p = 0,655) and population density (p = 0,387) with DHF incidence in Tembalang District at 2019.